Analysis of the experience of public-private partnership projects in Kazakhstan and its development potential - Mambetova, S.Sh.; Akhmetova, A.S.; Yeskerova , Z.A. (BUKETOV BUSINESS REVIEW, 2018)
In general, the general characteristics of WTO models are analyzed in the analysis of projections realized in the frames of partner relations in the state and private sectors. The first projects of the Concession were first modeled by this model, and this model was vybrana and realistically effective. In either case, the VTO also has a contract, such as a private company, a local authority. In the modeling of the Model of Concession and Model of BOT, the project was studied during the construction of the school and the children ’s bays. In this connection, the model will be used as a precedent for the recovery of the concessionaire, which will cover the expense of investing, exploiting the plant for the production of children’s orphanages and school projects. At the present time, the importance and indifference of large-scale concession projects in Kazakhstan. In 2015, the new law on state-private partnerships, the new impulse of the state and business in Kazakhstan. As a result, the BOT model has been evaluated for the GHC project for the construction and operation of children’s nursing bottles, the BOT in the area of healthcare and in the project water supply.